Read me Romania! (Confluenţe Bibliologice, 2012)
The article presents the successful activity of Oscar Print publishing house beginning in 1993 when it was founded. The author reveals the editorial events worthy of being known for professionals and amateurs of history and national art.
Keywords: Oscar Print Publishing House